Microstructure and micromorphology of Cu/Co nanoparticles: Surface texture analysis - Ţălu, Ştefan; Bramowicz, Miroslaw; Kulesza, Slawomir; Ghaderi, Atefeh; Dalouji, Vali; Solaymani, Shahram; Khalaj, Zahra (Electronic materials letters, 2016)
This paper analyses the three-dimensional (3-D) surface texture of Cu/Co thin films deposited by DC-Magnetron sputtering method on the silicon substrates. The prepared Cu/Co nanoparticles were used as research materials. Three groups of samples were deposited on silicon substrates in the argon atmosphere and gradually cooled down to room temperature. The crystalline structures and elemental compositions were analyzed by X-ray diffraction (XRD) spectrum with conventional Bragg-Brentano geometry. X-ray diffraction profile indicates that Co and Cu interpenetrating crystalline structures are formed in these films. The sample surface images were recorded using atomic force microscopy (AFM) and analyzed by means of the fractal geometry. Statistical, fractal and functional surface properties of prepared samples were computed to describe major characteristics of the spatial surface texture of Cu/Co nanoparticles. Presented deposition method is a versatile, costeffective, and simple method to synthesize nano- and microstructures of Cu/Co thin films. This type of 3-D morphology allows to understand the structure/property relationships and to investigate defect-related properties of Cu/Co nanoparticles. Presented results confirm the possibility of preparing high-quality Cu/Co nanoparticles via DC-Magnetron sputtering method on silicon substrates.